Answer:
See below.
Step-by-step explanation:
-7(6) = -42
-1(-10) = 10
2(-5) = -10
-3(-14) = 42
-32/-4 = 8
-2(-2)(-2) = -8
Answer:
Solution (7,1)
Step-by-step explanation:
Use the elimination method
x + y=8
x - y=6
--------------Add
2x = 14
x = 7
Substitute x = 7 into x + y=8
7 + y=8
y = 8 - 7
y = 1
Solution (7,1)
Upon a slight rearrangement this problem gets a lot simpler to see.
x^3-x+2x^2-2=0 now factor 1st and 2nd pair of terms...
x(x^2-1)+2(x^2-1)=0
(x+2)(x^2-1)=0 now the second factor is a "difference of square" of the form:
(a^2-b^2) which always factors to (a+b)(a-b), in this case:
(x+2)(x+1)(x-1)=0
So g(x) has three real zero when x={-2, -1, 1}
Answer:
3 is the coefficient of m3
Answer:
I don't know
because I just want ask my question in this app